Pitcher aging affects throwing shoulder biomechanics and proprioception: The Italian experience - Pegreffi, F.; Vittori, L.; Foschi, E.; Latessa Maietta, P.; Paladini, P.; Campi, F.; Pellgrini, A.; Porcellini, G.; Tentoni, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Baseball is a sport increasingly practiced in Italy. The pitcher is at risk from repetitive stress on the dominant upper arm. Because of this, pitchers train far more on the dominant arm leading to asymptomatic biomechanical changes. The purpose of this study was to compare shoulder intra/extra rotational power and shoulder motor skill in young and senior athletes. Methods: Twenty right-hand healthy pitchers playing for at least four years were recruited : Group A (12±2yrs) and Group B (24±1yrs). Subjects with a history of shoulder dislocation, shoulder surgery or structural injuries to the shoulder complex were excluded from the study. Isokinetic tests (IT) were performed to evaluate intra/extra rotational power, and shoulder motor skill test (SMST) to evaluate proprioception. Results: Performing IT, we have found in both groups a significant higher external rotation compared to internal rotation in the throwing shoulder (TS), while in the contralateral shoulder (CS) the balance was preserved ( p<0.003). In Group A, SMST was 4±2 points (TS) and 4±1 points (CS), p=n.s. In Group B, SMST was 9±1 points (TS) and 4±2 points (CS), p<0.005. Discussion and Conclusion: Italian pitchers demonstrated a higher external rotational power in the throwing shoulder after only four years of practicing baseball. Motor skill ability seems to develop later in the dominant shoulder. This study suggests that a baseball training program, especially for young pitchers, should include not only exercises to restore internal/external rotation balance but also motor skill exercises, to improve throwing ability, limit the number of throws, prevent shoulder injury over time.